Porphyrin‐POSS Molecular Hybrids. Issue 38 (26th August 2013) - Sun, Junshan; Chen, Yanli; Zhao, Luyang; Chen, Yuting; Qi, Dongdong; Choi, Kyung‐Min; Shin, Dong‐Soo; Jiang, Jianzhuang
<x xml:space="preserve">Abstract</x> Porphyrin‐POSS hybrid: Porphyrin‐POSS molecular hybrid composites (see scheme; POSS = polyhedral oligomeric silsesquioxanes) were synthesized and structurally characterized, allowing the realization of truly homogenous dispersion of basic functional building blocks between organic and inorganic components at the molecular level. These materials allow the optimization of aggregation/association behavior and thus the functional optical properties of the porphyrinato zinc compounds.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>